Diphtheria, pertussis, and tetanus vaccine-induced extensive longitudinally extensive transverse myelitis: A case report (Indian Journal of Case Reports, 2019)
Transverse myelitis (TM) has been reported in association with vaccination, including post-diphtheria, pertussis, and tetanus (DPTw) vaccination. Here, we report the case of a 21-month-old female child presented with loss of neck control with a history of DPTw booster vaccination approximately 4 weeks before this illness. The child was referred to the tertiary care service hospital. Magnetic resonance imaging of the spine revealed longitudinally extensive TM in the cervical segment. Extensive investigation effectively excluded causes other than vaccination-associated TM. Following treatment with corticosteroids and intravenous immune-globulin, the child had a complete recovery. Early diagnosis and prompt treatment with immunotherapy are associated with a good outcome.